Cal‘MAM’ity at the Endoplasmic Reticulum-Mitochondrial Interface: A Potential Therapeutic Target for Neurodegeneration and Human Immunodeficiency Virus-Associated Neurocognitive Disorders - Proulx, Jessica; Park, In-Woo; Borgmann, Kathleen (Frontiers in Neuroscience, 2021)
The endoplasmic reticulum (ER) is a multifunctional organelle and serves as the primary site for intracellular calcium storage, lipid biogenesis, protein synthesis, and quality control. Mitochondria are responsible for producing the majority of cellular energy required for cell survival and function and are integral for many metabolic and signaling processes. Mitochondria-associated ER membranes (MAMs) are direct contact sites between the ER and mitochondria that serve as platforms to coordinate fundamental cellular processes such as mitochondrial dynamics and bioenergetics, calcium and lipid homeostasis, autophagy, apoptosis, inflammation, and intracellular stress responses. Given the importance of MAM-mediated mechanisms in regulating cellular fate and function, MAMs are now known as key molecular and cellular hubs underlying disease pathology. Notably, neurons are uniquely susceptible to mitochondrial dysfunction and intracellular stress, which highlights the importance of MAMs as potential targets to manipulate MAM-associated mechanisms. However, whether altered MAM communication and connectivity are causative agents or compensatory mechanisms in disease development and progression remains elusive. Regardless, exploration is warranted to determine if MAMs are therapeutically targetable to combat neurodegeneration. Here, we review key MAM interactions and proteins both in vitro and in vivo models of Alzheimer’s disease, Parkinson’s disease, and amyotrophic lateral sclerosis. We further discuss implications of MAMs in HIV-associated neurocognitive disorders (HAND), as MAMs have not yet been explored in this neuropathology. These perspectives specifically focus on mitochondrial dysfunction, calcium dysregulation and ER stress as notable MAM-mediated mechanisms underlying HAND pathology. Finally, we discuss potential targets to manipulate MAM function as a therapeutic intervention against neurodegeneration. Future investigations are warranted to better understand the interplay and therapeutic application of MAMs in glial dysfunction and neurotoxicity.